2019
DOI: 10.1152/ajpheart.00478.2019
|View full text |Cite
|
Sign up to set email alerts
|

BDNF downregulates β-adrenergic receptor-mediated hypotensive mechanisms in the paraventricular nucleus of the hypothalamus

Abstract: Brain derived neurotrophic factor (BDNF) is an important modulator of neuronal function, capable of mediating long‐term changes in neuronal structure and signaling in the central nervous system (CNS). Increased expression of BDNF in the PVN has been associated with elevated blood pressure (BP) and sympathetic nervous system activity. However, the mechanism mediating this effect of BDNF is unclear. BDNF is a modulator of catecholaminergic (CA‐ergic) neuronal function in the CNS, and could potentially influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 91 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…Of note, higher α 1A -adrenoceptor mRNA [85] and unchanged α 1A , α 1B or α 1Dadrenoceptor mRNA [86,87] levels in the PVN of animals submitted to different experimental models of chronic hypertension have been reported. Chronic stress sensitizes the HPA axis to further acute stress (as measured by transient plasma ACTH increase) in rats, altogether with enhancing the response to α 1 -adrenergic receptor activation in the PVN [64].…”
Section: Pvn As the Output System That Mediates Hypertension And Incr...mentioning
confidence: 99%
“…Of note, higher α 1A -adrenoceptor mRNA [85] and unchanged α 1A , α 1B or α 1Dadrenoceptor mRNA [86,87] levels in the PVN of animals submitted to different experimental models of chronic hypertension have been reported. Chronic stress sensitizes the HPA axis to further acute stress (as measured by transient plasma ACTH increase) in rats, altogether with enhancing the response to α 1 -adrenergic receptor activation in the PVN [64].…”
Section: Pvn As the Output System That Mediates Hypertension And Incr...mentioning
confidence: 99%
“…For example, α 1D up-regulates while the α 1A and α 1B subtypes down-regulate in a concentration-dependent manner during an agonist challenge (i.e., endogenous noradrenaline), and down-regulation of the latter was accompanied by reductions of mRNA (for review see [ 154 ]). Interestingly, higher levels of α 1A -adrenoceptor mRNA have reported in the PVN of rats suffering from chronic hypertension [ 155 ], but unchanged α 1A , α 1B , or α 1D -adrenoceptor mRNA in the whole hypothalamus [ 156 ] and the VPN [ 157 ] has also been reported. Besides, chronic stress (which is often accompanied by hypertension) sensitizes the HPA axis to further acute stress (as measured by transient plasma ACTH increase) in rats, enhancing the response to α 1 -adrenergic receptor activation in the PVN [ 158 ].…”
Section: Pvn As the Output System That Mediates Hypertension And Incr...mentioning
confidence: 99%
“…The paraventricular nucleus (PVN) of the hypothalamus plays an important role in regulating SNA [19]. Recent studies showed that increased levels of the brain-derived neurotrophic factor (BDNF) in the PVN led to increased sympathetic activity, BP, and arrhythmia [20][21][22][23]. Interestingly, miR-204 is highly expressed in the hypothalamus.…”
Section: Hypothalamic Mir-204 and Sympathetic Nerve Outputmentioning
confidence: 99%